2001
DOI: 10.1530/rep.0.1210077
|View full text |Cite
|
Sign up to set email alerts
|

Stage-specific and differential expression of gap junctions in the mouse ovary: connexin-specific roles in follicular regulation

Abstract: ResearchGap junction communication plays an essential role in follicle growth. Immunocytochemistry and confocal microscopy were used to examine the expression of gap junction connexins of the α and β subfamilies in follicles from primordial to preovulatory stages in the ovaries of prepubertal and adult mice. Connexin-specific antibodies detected α 1 , α 4 , α 6 , β 1 , β 2 and β 4 connexins within follicles. In adult ovaries connexin immunolabelling was stronger in larger (more mature) follicles than it was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
72
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(83 citation statements)
references
References 8 publications
9
72
2
Order By: Relevance
“…19), Cx43 is the only gap junction protein that has been clearly shown to be expressed by the granulosa cells of early preantral follicles of the mouse (17,37). Thus the follicle arrest in Cx43-deficient ovaries may be due to a complete absence of connexins from the granulosa cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19), Cx43 is the only gap junction protein that has been clearly shown to be expressed by the granulosa cells of early preantral follicles of the mouse (17,37). Thus the follicle arrest in Cx43-deficient ovaries may be due to a complete absence of connexins from the granulosa cells.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these results suggest that the granulosa cells of preantral follicles express one or more connexins other than Cx43 but that this other connexin does not normally assemble into functional gap junctions in the absence of Cx43. The other connexin(s) could be Cx32, Cx37, Cx45, or Cx57, all of which are reported to be expressed along with Cx43 in granulosa cells of mature mouse follicles (19,37). Such a rare connexin, coexpressed with Cx43 in granulosa cells of early follicles, might contribute more significantly to gap junction assembly later in folliculogenesis as gap junctions become larger and more numerous.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proteins connexins is the principle component of gap junction. It has been demonstrated that connexins 32, 37, 43, 45 and 57 have been detected within growing and mature mouse follicles (Wright et al, 2001). However, in cattle, connexin expression shows in a stage specific manner; for instance, Cx26 is expressed in oocytes of primordial, primary and secondary follicles and in the granulosa of healthy antral follicles (Johnson et al, 1999).…”
Section: Cell-cell Communication During Follicular Developmentmentioning
confidence: 99%
“…Similarly, a PKC-dependent phosphorylation of Cx43 that correlates with a reduction of gap junction coupling was found during G2/M phase of the cell cycle [11] GFSHR-17 granulosa cells, the in vitro model for granulosa cells of the maturing ovular follicle, are a suitable cell system for the analysis of gap junction coupling and apoptosis [12]. They form gap junction channels mainly formed by Cx43 and Cx45 [13], which regulate follicular development and atresia [14][15][16]. Moreover, granulosa cells in the ovular follicles are eliminated by apoptosis during atresia or the deterioration of the corpus lu-teum [17,18].…”
Section: Introductionmentioning
confidence: 99%